Targeting cryptic allosteric sites of G protein-coupled receptors as a novel strategy for biased drug discovery - Xin Qiao; Xiaolong Li; Mingyang Zhang; Ning Liu; Yanmei Wu; Shaoyong Lu; Ting Chen (Pharmacological Research)
G protein-coupled receptors (GPCRs) represent the largest family of membrane receptors and are highly effective targets for therapeutic drugs. GPCRs couple different downstream effectors, including G proteins (such as Gi/o, Gs, G12, and Gq) and β-arrestins (such as β-arrestin 1 and β-arrestin 2) to mediate diverse cellular and physiological responses. Biased signaling allows for the specific activation of certain pathways from the full range of receptors’ signaling capabilities. Targeting more variable allosteric sites, which are spatially different from the highly conserved orthosteric sites, represents a novel approach in biased GPCR drug discovery, leading to innovative strategies for targeting GPCRs. Notably, the emergence of cryptic allosteric sites on GPCRs has expanded the repertoire of available drug targets and improved receptor subtype selectivity. Here, we conduct a summary of recent progress in the structural determination of cryptic allosteric sites on GPCRs and elucidate the biased signaling mechanisms induced by allosteric modulators. Additionally, we discuss means to identify cryptic allosteric sites and design biased allosteric modulators based on cryptic allosteric sites through structure-based drug design, which is an advanced pharmacotherapeutic approach for treating GPCR-associated diseases.